Enhanced DNA damage response through RAD50 in triple negative breast cancer resistant and cancer stem-like cells contributes to chemoresistance - Abad, Etna; Civit, Laia; Potesil, David; Zdrahal, Zbynek; Lyakhovich, Alex (The FEBS journal, 2021)
A growing body of evidence supports the notion that cancer resistance is driven by a small subset of cancer stem cells (CSC), responsible for tumor initiation, growth, and metastasis. Both CSC and chemoresistant cancer cells may share common qualities to activate a series of self-defense mechanisms against chemotherapeutic drugs. Here, we aimed to identify proteins in chemoresistant triple-negative breast cancer (TNBC) cells and corresponding CSC-like spheroid cells that may contribute to their resistance. We have identified several candidate proteins representing the subfamilies of DNA damage response (DDR) system, the ATP-binding cassette, and the 26S proteasome degradation machinery. We have also demonstrated that both cell types exhibit enhanced DDR when compared to corresponding parental counterparts, and identified RAD50 as one of the major contributors in the resistance phenotype. Finally, we have provided evidence that depleting or blocking RAD50 within the Mre11-Rad50-NBS1 (MRN) complex resensitizes CSC and chemoresistant TNBC cells to chemotherapeutic drugs.
Keywords: DNA vazebné proteiny; Drug Resistance, Neoplasm; Doxorubicin; Nuclear Proteins; DNA Damage; Cyclophosphamide; cancer stem cells; cisplatina; Female; jaderné proteiny; Cisplatin; RAD50; ženské pohlaví; přežití bez známek nemoci; chemoresistance; homologní protein MRE11; triple-negative breast cancer; lidé; triple-negativní karcinom prsu; chemorezistence; enzymy opravy DNA; Triple Negative Breast Neoplasms; hydrolasy působící na anhydridy kyselin; Acid Anhydride Hydrolases; DNA Repair Enzymes; Cell Cycle Proteins; poškození DNA; MRE11 Homologue Protein; Neoplastic Stem Cells; doxorubicin; DNA-Binding Proteins; Disease-Free Survival; DNA damage repair; proteiny buněčného cyklu; cyklofosfamid; nádorové kmenové buňky; Humans